1995
DOI: 10.1016/0008-6363(96)88579-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of HOE642, a selective sodium-hydrogen exchange subtype 1 inhibitor, on cardiac ischaemia and reperfusion

Abstract: HOE642 is a very selective NHE subtype 1 inhibitor showing cardioprotective and antiarrhythmic effects in ischaemic and reperfused hearts. Further development of well tolerated compounds like HOE642 could lead to a new therapeutic approach in clinical indications related to cardiac ischaemia and reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
146
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(155 citation statements)
references
References 0 publications
6
146
0
3
Order By: Relevance
“…HOE 642 (0.5 mg/kg) was administered intraperitoneally at 10 min, 24 and 48 h after HI (n = 8; 6 M, 2 F). Due to the short half-life of HOE 642, it was administered at multiple time points (half-life: 40 min in rats) [13]. The HI vehicle control animals received an equal volume of saline at the same time points (n = 9; 6 F, 3 M).…”
Section: Methodsmentioning
confidence: 99%
“…HOE 642 (0.5 mg/kg) was administered intraperitoneally at 10 min, 24 and 48 h after HI (n = 8; 6 M, 2 F). Due to the short half-life of HOE 642, it was administered at multiple time points (half-life: 40 min in rats) [13]. The HI vehicle control animals received an equal volume of saline at the same time points (n = 9; 6 F, 3 M).…”
Section: Methodsmentioning
confidence: 99%
“…Cariporide, which is a high selective and low cytotoxic NHE1 inhibitor [22], was used to decrease the pH i . This study was aimed to explore the effect of decreased pH i on the differentiation of hUC-MSCs and to explore the putative mechanism involved.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has shown that insulin action on GLUT4 translocation and NHE1 activity are intricately linked, demonstrated by the finding that NHE1 activity is required for optimal GLUT4 translocation [17]. Cariporide, an NHE inhibitor [22], prevented the insulin-induced cytosol alkalinization and the associated insulin-stimulated GLUT4 translocation and glucose uptake [17]. …”
Section: Introductionmentioning
confidence: 99%